Hubungan Pijat Oksitosin Terhadap Proses Pengeluaran Asi Pada Ibu Post Partum Di Puskesmas Pattoppakang Kabupaten Takalar - Kartini. H, Anita; Sumarmi, Sumarmi; Ernawati, Ernawati; Sah Puteri, sri Kurnia (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Background: This research aims to analyze the relationship between oxytocin massage and the smooth process of breastfeeding in the Pattopakang Community Health Center, Takalar Regency in 2023. Research Method: This type of research is a quantitative research with a one group pre test-post test design approach. This research was conducted in Pattoppakang Community Health Center area, Takalar Regency with a population of 47 people and a sample of 32 people. The sample collection technique used was purposive sampling. The independent variable is oxytocin massage. The dependent variable is the smooth flow of breast milk in post partum mothers. Data was collected using an observation sheet. Data processing uses Editing, Coding, Scoring, Tabulating and statistical tests use the Paired Samples Test statistical test. Results: the research is presented in the form of tables and narratives. The results of this research were obtained from 32 respondents, before the oxytocin massage, most of the respondents had 3 breast milk output smoothly. (9.4%), 29 (90.6%) were less than fluent, after oxytocin massage, the majority of respondents expressed breast milk smoothly, 30 mothers (93.8%). The Paired statistical test shows that the p value = 0.001 < a (0.05) so that H1 is accepted. The conclusion is that there is an influence of oxytocin massage on the smooth flow of breast milk in the Pattopakang health center area, Takalar district. Discussion: It is recommended that the management of the community health center provide better counseling or guidance about oxytocin massage to every postpartum